DISTINCTIVE FEATURE OF SPORTS MANAGEMENT AND ITS ROLE OF SPORT AREA - Abbasov Baxadir Asatillayevich (American Journals, 2023)
Sports management is one of the types of industry-specific management that deals with the management of sports organizations. In connection with this approach, organization is a key concept of sports management. From the point of view of management, physical culture and sport are not only "appropriate human motor activity", not only a set of special tools and methods for the directed development of physical capacity of people, as stated in the theory of physical culture.
Keywords: Sport, management, sport theory, sport organization, competition, social management, sport culture.